Spectrophotometric Determination of Levofloxacin in Pharmaceutical Formulations - Golcu, A.; Dolaz, M.; Kocak, B.; Kavak, N.; Demirelli, H. (Asian Journal of Chemistry, 2010)
A simple, sensitive and accurate spectrophotometric method has been developed for the assay of levofloxacin (LEVO), which is based on the complexation of drug with copper(II) at pH 5.0, using Britton- Robinson (BRT) buffer solution, to produce a green adduct. Developed spectrophotometric method was compared with UV-spectrophotometric method. The absorbances were measured at 581.13 nm and 299.15 nm for proposed method and UV-spectrophotometric method, respectively. The stoichiometric ratio of levofloxacin to Cu(II) ions in the chromophoric complex was also determined to be 1:1 by Job's method. The optimum conditions for Cu(II)-LEVO complex(1:1) were ascertained and a spectrophotometric method was developed for the determination of levofloxacin in the concentration range 8.0-160.0 g mL-1, the detection limit being 2.3 g mL-1. The method was validated for the direct determination of levofloxacin in tablet dosage formulations. The repeatability, reproducibility, precision and accuracy of the method was also investigated. The protonaion constants of the levofloxacin and stability constants of its Cu(II) complexes were also determined by potentiometric titration method in 50 % methanol-water mixtures at 25.00 ± 0.02 ºC under nitrogen atmosphere and ionic strength of 0.10 M sodium chloride. It has been observed that levofloxacin has two protonation constants. It was found that the divalent metal ion Cu(II) was formed CuL, CuL2, Cu2L2 and Cu2L stable complexes with levofloxacin by potentiometric method.